Stochastic seismic analysis of hydrodynamic pressure in dam reservoir systems. - Di Paola, M.
Hydrodynamic seismic induced pressure requires careful consideration in the aseismic design of dams. Effects induced by earthquake excitation may cause many fold increments of hydrostatic pressure. In this study earthquake excitation has been modelled by means of random process theory obtaining the response statistics of a dam reservoir dynamical system. The analysis has been conducted assuming a rigid retaining wall of the reservoir and dissipative fluid.
Keywords: Dam reservoir system; Stochastic analysis; Hydrodynamic pressure